Narcissism among students of the College of Medicine and students of the College of Agriculture - University of Al-Qadisiyah (Journal of the College of Basic Education, 2022)
The current research aimed to know the level of narcissism among students of the Faculty of Medicine and students of the Faculty of Agriculture, and the results showed that the students of the Faculty of Medicine and the Faculty of Agriculture enjoy a level of narcissism. The level of narcissism. Perhaps the status that women enjoy today, the degree of self-confidence and society's view of them led to this result, and this result contradicted previous studies. There are statistically significant differences due to the variable of specialization and in favor of the students of the Faculty of Medicine, and this is a natural result of these students' feeling of superiority over the rest of their peers.